Supporting Nurse’s Unseen Decision-Making Needs: A Human-Centered Innovation Case Study - Babalola, Grace; Jesso, Stephanie Tulk (Proceedings of the International Symposium of Human Factors and Ergonomics in Healthcare, 2025)
Despite nurses' critical role in healthcare delivery and patient outcomes, current technologies often overlook their specific decision-making needs, focusing instead on obvious issues while neglecting frontline staff requirements. This gap results in inefficient workflows, decision-making delays, and burnout among nursing professionals. Using the TripTech human-centered design method, we conducted interviews, need-based surveys, and focus group discussions with nurses across multiple U.S. states to identify key needs and evaluate proposed solutions for a novel nurse-centered information platform. Results identified key needs including rapid access to patient information, evidence-based practice updates, peer support during critical situations, and mental health resources. Six design concepts were developed and evaluated, with nurses strongly favoring platforms offering real-time patient information access, research collaboration tools, and specialized training resources. Critical design requirements emerged: seamless workflow integration, verified evidence-based content, secure peer collaboration, strict privacy standards, and specialty customization options. This research demonstrates the value of user-centered design in healthcare technology development and provides direction for creating tools that support nurses' complex decision-making needs.